Epidemic history investigation: a new method of finding close contacts - Li, Xin; Li, Yalan; Liu, Tianjiao; Ding, Rui; Hou, Qiannan; Xiong, Liling; Du, Na; Gong, Zhaolin; Cheng, Linbo; Luo, Dan; Wei, Sumei; Yang, Xiao (Frontiers in Public Health, 2023)
Introduction: Coronavirus disease 2019 has become a major global public health concern in December 2019. However, finding and excluding close contacts of COVID-19 infectors is a critical but difficult issue. This study aimed to introduce a new method of epidemiological investigation named space-time companions, which was adopted in Chengdu, China, in November 2021. Methods: An observational investigation was conducted during a small outbreak of COVID-19 in Chengdu, China in November 2021. A flow chart was used to describe the screening process of spatiotemporal companions in detail and illustrate the space-time companion epidemic management method. Results: The COVID-19 epidemic outbreak in Chengdu was effectively controlled for approximately one incubation period (14 days). After four rounds of space-time companions screening, more than 450,000 space-time companions were screened, including 27 COVID-19 infectors. Moreover, in the subsequent rounds of nucleic acid testing for all people in the city, no infected person was found proving the end of this epidemic outbreak. Conclusion: The space-time companion provides a new idea for screening close contacts of the COVID-19 infector and other similar infectious diseases, which may be a turning point from traditional artificial epidemiologic investigation to intelligent models.